2004
DOI: 10.1080/00016470410004148
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgically treated intraarticular calcaneus fractures—SF-36 compared with AOFAS and MFS

Abstract: Patients face significant limitations regarding general health after calcaneal fractures. The usual foot-scores measure only 2 dimensions of outcome: function and pain. To measure all dimensions of outcome, SF-36 is a better alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 8 publications
1
26
1
Order By: Relevance
“…Other investigators reported similar limitations in these categories compared with controls. 20 The fact that their patients also reported significantly reduced health perceptions and social functioning, contrary with our patients' favorable self perceptions, might be related to cultural and social differences between the populations. The "total" Short Form-36 score, representing the mean score of all components of the questionnaire was closely similar with others, 4 further supporting the generalizability of our study population.…”
Section: Discussioncontrasting
confidence: 52%
“…Other investigators reported similar limitations in these categories compared with controls. 20 The fact that their patients also reported significantly reduced health perceptions and social functioning, contrary with our patients' favorable self perceptions, might be related to cultural and social differences between the populations. The "total" Short Form-36 score, representing the mean score of all components of the questionnaire was closely similar with others, 4 further supporting the generalizability of our study population.…”
Section: Discussioncontrasting
confidence: 52%
“…To our knowledge, the advantages associated with the use of generic QOL questionnaires compared to disease-specific questionnaires are more variable. In previous studies, the SF-36 or sickness impact profile was a better indicator of health-related QOL in patients suffering from calcaneal fractures [27], systemic lupus erythematosus [28], epilepsy [29] or asthma [30]. On the contrary, although several generic QOL questionnaires including SF-36 were more comprehensive in coverage of different health status domains, the disease-specific QOL questionnaires had better psychometric properties than did the generic QOL questionnaires in coronary artery disease and congestive heart failure [31], or multiple sclerosis [32] and had a better ability to predict treatment outcome in total joint arthroplasty [33], carpal tunnel syndrome [34], peripheral arterial disease [35], transurethral resection of the prostate [36], carpal tunnel syndrome [37], chronic sinusitis [38] or varicose veins [39].…”
Section: Discussionmentioning
confidence: 98%
“…The MFS has broad current acceptance 35 and it has content validity for pain and physical function. In addition, the MFS showed better correlation with the concomitant use of SF-36 in the assessment of patient’s outcome when compared to the AOFAS Ankle Hindfoot Scale 35,36 . In MFS, it has 3 components which are the pain (45 marks), the functions (55 marks) and the motion (5 marks); and total maximum of 100 points.…”
Section: Methodsmentioning
confidence: 95%
“…It yields an 8-scale profile of functional health and well-being scores as well as psychometrically-based physical and mental health summary measures 36 . The Malay version of SF-36v2 has its generally acceptable internal consistency and validity 37 and is widely accepted.…”
Section: Methodsmentioning
confidence: 99%